DNA methylation-associated colonic mucosal immune and defense responses in treatment-naïve pediatric ulcerative colitis - Harris, R Alan; Nagy-Szakal, Dorottya; Mir, Sabina A V; Frank, Eibe; Szigeti, Reka; Kaplan, Jess L; Bronsky, Jiri; Opekun, Antone; Ferry, George D; Winter, Harland; Kellermayer, Richard (Epigenetics, 2014)
Inflammatory bowel diseases (IBD) are emerging globally, indicating that environmental factors may be important in their pathogenesis. Colonic mucosal epigenetic changes, such as DNA methylation, can occur in response to the environment and have been implicated in IBD pathology. However, mucosal DNA methylation has not been examined in treatment-naïve patients. We studied DNA methylation in untreated, left sided colonic biopsy specimens using the Infinium HumanMethylation450 BeadChip array. We analyzed 22 control (C) patients, 15 untreated Crohn's disease (CD) patients, and 9 untreated ulcerative colitis (UC) patients from two cohorts. Samples obtained at the time of clinical remission from two of the treatment-naïve UC patients were also included into the analysis. UC-specific gene expression was interrogated in a subset of adjacent samples (5 C and 5 UC) using the Affymetrix GeneChip PrimeView Human Gene Expression Arrays. Only treatment-naïve UC separated from control. One-hundred-and-twenty genes with significant expression change in UC (> 2-fold, P<0.05) were associated with differentially methylated regions (DMRs). Epigenetically associated gene expression changes (including gene expression changes in the IFITM1, ITGB2, S100A9, SLPI, SAA1, and STAT3 genes) were linked to colonic mucosal immune and defense responses. These findings underscore the relationship between epigenetic changes and inflammation in pediatric treatment-naïve UC and may have potential etiologic, diagnostic, and therapeutic relevance for IBD.
Keywords: ulcerózní kolitida; epigeneze genetická; Immunity, Mucosal; Male; mladiství; Epigenesis, Genetic; slizniční imunita; mužské pohlaví; studie případů a kontrol; DNA methylome; Crohnova nemoc; mladý dospělý; Intestinal Mucosa; epigenetics; ulcerative colitis; dítě; Child; DNA methylation; Colon; Child, Preschool; Young Adult; ženské pohlaví; Gene Expression; Humans; předškolní dítě; metylace DNA; kolon; expression; střevní sliznice; Crohn Disease; DNA Methylation; Pediatric inflammatory bowel disease; exprese genu; Female; treatment naïve; Adolescent; Colitis, Ulcerative; lidé; Case-Control Studies